Fermi Large Area Telescope Performance after 10 Years of Operation - Ajello M; Atwood WB; Axelsson M; Bagagli R; Bagni M; Baldini L; Bastieri D; Bellardi F; Bellazzini R; Bissaldi E; Bloom ED; Bonino R; et al. (IOP PUBLISHING LTD, 2022)
The Large Area Telescope (LAT), the primary instrument for the Fermi Gamma-ray Space Telescope (Fermi) mission, is an imaging, wide field-of-view, high-energy gamma-ray telescope, covering the energy range from 30 MeV to more than 300 GeV. We describe the performance of the instrument at the 10 yr milestone. LAT performance remains well within the specifications defined during the planning phase, validating the design choices and supporting the compelling case to extend the duration of the Fermi mission. The details provided here will be useful when designing the next generation of high-energy gamma-ray observatories.